Leadership, Faculty Behaviour, and Educational Supply Chain Management: A Systemic Model for Fostering Entrepreneurial Intentions in Higher Education - Yadav, Mohit; Srivastava, Anugamini Priya; Alyousef, Muna I.; Naim, Mohammad Faraz; Amoozegar, Azadeh (International Journal of Learning, Teaching and Educational Research, 2026)
This paper examines the impact of genuine transformational leadership on entrepreneurial intentions of students in the context of educational supply chain management, based on the Theory of Planned Behavior. The study formulates propositions by reviewing literature on leadership, teacher traits and entrepreneurship education to provide the relationship between leadership and the entrepreneurial innovation intentions, academic optimism and organizational citizenship behavior of the students. It emphasizes the contribution of academic optimism in the explanation of the influence of leadership on teachers and students. The paper provides a unified conceptual framework that may be used in future empirical studies and demonstrates how universities can nurture entrepreneurial attitudes and innovative practices with the help of successful leadership. The results offer useful suggestions to academic faculty who want to foster the entrepreneurial potential of students and suggest the way to conduct research. This work bridges leadership, education management and entrepreneurship, which provides a new approach to innovation promotion among students and enhances the effectiveness of higher education institutions. https://doi.org/10.26803/ijlter.25.1.44